Substantial Justice in the Court's Decision to Annul an Authentic Deed - Nurhaliza Setyawan, Aqiila; Santoso, Bambang; Andi Fitriono, Riska (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2026)
Agreements can be made in writing in the form of an authentic deed. A notary is an official authorized to create an authentic deed. The creation of an authentic deed must comply with the provisions of the Law.Number 2 of 2014 concerning the Position of Notary Public amends Law No. 30 of 2004 concerning the Position of Notary Public. In Decision Number 19/Pdt.G/2024/PN.Mks, the Judge declared the authentic deed, namely the Power of Attorney to Sell land made before a Notary, null and void because it was made without the knowledge of one of the parties. However, the Notary was not punished by the judge. This study focuses on discussing whether the judge's decision has reflected substantial justice. This study uses a legal research method with a prescriptive nature, and uses a case approach and a conceptual approach. The legal material analysis technique used is the deductive logic method with a syllogistic mindset. Aristotle's theory of justice states that justice is something that is assessed proportionally according to its role. Therefore, when viewed from Aristotle's theory of justice, the decision that the Notary was not punished for making a Power of Attorney to Sell without the knowledge of one of the parties does not provide substantial justice for the plaintiff. However, the judge could not make such a decision because the imposition of punishment on the notary was not requested in the petitum and he was bound by the principle of Iudex Non Ultra Petita. The principle of Iudex Non Ultra Petita stipulates that the judge cannot decide anything beyond what is requested in the petitum.